HUBUNGAN PERSEPSI SISWA TENTANG KOMPETENSI GURU DENGAN SIKAP SOSIAL DAN HASIL BELAJAR SISWA - Mabrotul Hikmah; Lina Listiana; Peni Suharti (Pedago Biologi : Jurnal Pendidikan dan Pembelajaran Biologi, 2017)
Teachers must have academic qualifications and competence as a learning agent. Academic qualification meant is the minimum educational level to be met by an educator. Competency as learning agents in elementary and high educations includes four competencies, namely pedagogical competence, personal competence, and professional competence and social competence. This research aims to determine the relationship between students’ perception about teachers’ competence with social attitudes and students’ learning outcomes. This research used descriptive analysis and correlation methods in which these methods are supported by data collection techniques include questionnaires, interviews, and documentation. Data analysis technique used in this research is product moment technique. Based on the data processing result obtained that the next step was classified and produced so that the final data produced Rxy as follows: on Muhammadiyah 1 Senior High School Surabaya, it has obtained the results of students perceptions teachers’ competence with social attitudes and students’ learning outcomes Ro of 0.99 and 0.81 whereas in Muhammadiyah 7 Senior High School Surabaya in consecutive obtained Ro of 0.40 and 0.75. Both of these data showed a positive correlation between student perceptions teachers’ competence with social attitudes and students’ learning outcomes. Thus, it can be concluded that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected, it does show that student perceptions teachers’ competence relating to social attitudes and students’ learning outcomes.Keyword: learning outcomes, student perceptions, teacher competence, social attitudes.